NETWORK COMMUNITIES WITH UNIVERSITY PARTICIPATION: ESTABLISHED PRACTICES OF SOCIAL INTERACTION - Mark V. Romm; Raisa A. Zayakina (Высшее образование в России)
The article analyzes a system of social interaction practices which are used by national universities to undertake their network activity in daily life. Taking into consideration value and goal orientation, the authors reveal obvious and hidden motives for university's choice between interaction practices in network communities. The authors' classification of the principles specifying the nature of interaction between actors in network communities is suggested. In accordance with the present classification, social practices of network partnership, network competition, and network simulator are suggested. On the basis of the proposed classification, expectant beneficiaries of network activity inside community are described. The authors study the mechanism of forming network simulators in research and education space and the phenomenon of network collapse as an inevitable consequence of their existence. The reasons for emergence of network simulacra in social networks with university participation are explored.